2011
DOI: 10.1038/ng.941
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and large-scale follow up identifies 16 new loci influencing lung function

Abstract: Pulmonary function measures reflect respiratory health and predict mortality, and are used in the diagnosis of chronic obstructive pulmonary disease (COPD). We tested genome-wide association with the forced expiratory volume in 1 second (FEV1) and the ratio of FEV1 to forced vital capacity (FVC) in 48,201 individuals of European ancestry, with follow-up of top associations in up to an additional 46,411 individuals. We identified new regions showing association (combined P<5×10−8) with pulmonary function, in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
433
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(467 citation statements)
references
References 54 publications
28
433
2
4
Order By: Relevance
“…Furthermore, NDUFC2 may represent a novel oncogene involved in breast cancer and intestinal adenocarcinoma, predicting poor prognosis 39, 40. Notably, the pathological relevance of NDUFC2/rs11237379 has been also highlighted through genome‐wide association studies in pulmonary disease 41, 42…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NDUFC2 may represent a novel oncogene involved in breast cancer and intestinal adenocarcinoma, predicting poor prognosis 39, 40. Notably, the pathological relevance of NDUFC2/rs11237379 has been also highlighted through genome‐wide association studies in pulmonary disease 41, 42…”
Section: Discussionmentioning
confidence: 99%
“…Positively selected genes had a significantly higher ratio of nonsynonymous substitutions to synonymous substitutions than other genes in the high-altitude snub-nosed monkeys (P = 3.84 × 10 −3 for R. strykeri, 3.45 × 10 −6 for R. bieti, and 5.10 × 10 −8 for R. roxellana) (Supplementary Table 8). Further examination of these 16 genes found that 6 genes, including ARMC2, NT5DC1, RNASE4, CDT1, RTEL1, and DNAH11, have functional associations with lung function, angiogenesis, DNA repair, or respiratory cilia movement, suggesting a role in the high-altitude adaptation of the snub-nosed monkeys [19][20][21][22][23][24] (Table 1). Moreover, when the common substitutions for these six genes were examined in more mammalian species with publicly available genomes, no identical substitutions were found in those species (Supplementary Table 9 and Supplementary Note).…”
Section: Volume 48 | Number 8 | August 2016 Nature Genetics L E T T Ementioning
confidence: 99%
“…Both LTL (11) and lung function (12,13) are known to be genetically regulated, and specific genes have been identified through genome-wide associations studies (14), but the known genes account for only a fraction of the heritable component estimated from family and twin data. Inter-individual variation in the amount and rate of decline with age both in lung function and in LTL has been less studied, although it is known to be affected by both genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%